(untitled) (International Journal of Food and Nutritional Sciences, 2019)
NITI Aayog embodies a paradigm shift in India’s governance structure, emphasizing cooperative federalism, strategic planning, and innovation. This abstract outline key aspects of NITI Aayog’s functioning, its achievements, and challenges. NITI Aayog serves as a platform for cooperative federalism, bringing together Chief Ministers from all states and union territories in its governing council.